Boundary layer flow of three-dimensional viscoelastic nanofluid past a bi-directional stretching sheet with Newtonian heating - M. Ramzan; Farhan Yousaf (AIP Advances, 2015)
This paper deals with steady three dimensional boundary layer flow of an incompressible viscoelastic nanofluid flow in the presence of Newtonian heating. An appropriate transformation is employed to convert the highly non linear partial differential equations into ordinary differential equations. Homotopy Analysis method (HAM) is used to find series solution of the obtained coupled highly non linear differential equations. The convergence of HAM solutions is discussed via h-curves. Graphical illustrations displaying the influence of emerging parameters on velocity, temperature and concentration profiles are given. It is observed that γ the conjugate parameter for Newtonian heating show increasing behavior on both temperature and concentration profiles. However, the temperature and concentration profiles are increasing and decreasing functions of Brownian motion parameter Nb respectively.